Evaluating Data from A Work Engagement Intervention among Nigerian History Lecturers - Boitumelo Molebogeng Diale; Chiedu Eseadi (Kuras Institute, 2022)
History lecturers who approach their work positively are more likely to be more engaged in their work than those who do not. Nigerian history lecturers have not been examined in terms of how psychological interventions can improve their work engagement. The present research examined the research dataset of an online rational emotive behavior therapy (online REBT) on work engagement among Nigerian history lecturers at higher education institutions. The sample consisted of 31 history lecturers, 16 of whom were randomly assigned to the online REBT group and 15 to a waiting-list control group. A repeated measures ANOVA was conducted at a level of 0.05 probability using IBM Statistical Package for Social Sciences software. Comparing the two groups, the dataset shows that history lecturers in the online intervention group exhibited significantly higher work engagement scores than those in the waiting list control group (p=.000). The one-month follow up dataset reveal that history lecturers who participated in the online REBT intervention continued to feel engaged at work compared to those in the waiting list control group (p=.000). Thus, a significant improvement in work engagement scores of history lecturers was associated with the online REBT intervention. Future studies with a larger sample size are needed.